First report of Colletotrichum aenigma and C. perseae causing anthracnose disease on Capsicum annuum in Israel. (February 2022) - Sharma, Gunjan; Maymon, Marcel; Elazar, Meirav; Freeman, Stanley
Abstract: Anthracnose caused by Colletotrichum spp. is an important disease of pepper ( Capsicum annuum ), affecting fruits and the overall yield worldwide. The disease was recently observed for the first time in Israel in the summer of 2020. In this study, morphology, phylogenetic analysis using glutamine synthase ( gs ) and the intergenic region between apn2 and Mat1 - 2 genes ( ApMat ) sequences, and pathogenicity assays were conducted to characterize and identify the Colletotrichum isolates retrieved from symptomatic pepper fruits. This is the first report of Colletotrichum aenigma and C. perseae as pathogens of pepper anthracnose in Israel. Highlights: Anthracnose fruit rot of pepper was observed in two locations in Israel. Pathogen diagnosis was based on morphology and sequence analysis of ApMat and gs genes. Pathogens were confirmed by performing Koch's postulates. First report of C. aenigma and C. perseae causing pepper anthracnose in Israel. Colletotrichum aenigma was more aggressive in causing disease symptoms.